Monks and the Use of the Thai Language for Propagation in the 21st Century - Yanavetee (Khonchaiyaphum), Witthaya; Thongkliang, Phitphiboon; Tapwijit, Akekalak; Variddhiṭhãyĩ, Phramaha Songvit (Mahachula Academic Journal, 2024)
During the Buddha's time, the Buddha sent his disciples to propagate Buddhism for the first time. The Buddha said ‘Monks Go on a pilgrimage for the benefit of many people Preach the Dharma, beautiful in the beginning, beautiful in the middle and beautiful in the end, proclaim the chastity together with the meaning and consonants, completely pure. At present, there is a change in Thai culture and the language used in words that need to find meaning to get to the original idea. If it is a Pali word, one must look at the Tripitaka. Distortion caused by lack of education causing the words that entered Thai society to change their meaning from the original in the Pali language or in the Tripitaka. In this regard, if there is no clarity or correction, the language will continue to be misused. Up to the present day, Facebook is the most popular medium in daily life. As a result, more and more monks come to use Facebook. The behavior and characteristics of using Facebook of monks can be divided into 4 types:- (1) for information and communication technology, (2) to propagation the dharma, (3) for academic work and (4) for entertainment